2022
DOI: 10.3847/1538-4357/ac8fed
|View full text |Cite
|
Sign up to set email alerts
|

Temperature Structures Associated with Different Components of the Atmospheric Circulation on Tidally Locked Exoplanets

Abstract: Observations of time-resolved thermal emission from tidally locked exoplanets can tell us about their atmospheric temperature structure. Telescopes such as JWST and ARIEL will improve the quality and availability of these measurements. This motivates an improved understanding of the processes that determine atmospheric temperature structure, particularly atmospheric circulation. The circulation is important in determining atmospheric temperatures, not only through its ability to transport heat, but also becaus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 44 publications
0
4
0
Order By: Relevance
“…Mendonça (2020) analyzed the angular momentum and heat transport of hot Jupiters using a non-hydrostatic GCM and found that the heat can be transported downward by mean circulation and stationary waves. Hammond & Lewis (2021) and Lewis & Hammond (2022) analyzed the impact of the horizontal flow pattern on heat transport on a canonical hot Jupiter. Komacek et al (2022a) showed that a high-entropy interior and a large heat flux produce different horizontal temperature and flow structures than a low-entropy case.…”
Section: Importance Of Atmospheric Inhomogeneity On Cooling Hot Jupitersmentioning
confidence: 99%
See 1 more Smart Citation
“…Mendonça (2020) analyzed the angular momentum and heat transport of hot Jupiters using a non-hydrostatic GCM and found that the heat can be transported downward by mean circulation and stationary waves. Hammond & Lewis (2021) and Lewis & Hammond (2022) analyzed the impact of the horizontal flow pattern on heat transport on a canonical hot Jupiter. Komacek et al (2022a) showed that a high-entropy interior and a large heat flux produce different horizontal temperature and flow structures than a low-entropy case.…”
Section: Importance Of Atmospheric Inhomogeneity On Cooling Hot Jupitersmentioning
confidence: 99%
“…The horizontal weather patterns in the stratified region can also be understood within the framework of Helmholtz decomposition (Hammond & Lewis 2021;Lewis & Hammond 2022). The horizontal circulation can be decomposed into divergent (vorticityfree) and rotational (divergence-free) components.…”
Section: Weather Patternmentioning
confidence: 99%
“…These maps contain small-scale structure that is not present in the observed eclipse maps in Section 3. A chevron-like structure is present in all the GCM maps, which is commonly attributed to the temperature structure associated with equatorial Kelvin and Rossby waves (Matsuno 1966;Showman & Polvani 2011;Lewis & Hammond 2022). THOR, expeRT/MITgcm, and the RM-GCM each show cold "lobes" on the nightside, which are likely associated with stationary equatorial Rossby waves (Matsuno 1966;Showman & Polvani 2011;Lewis & Hammond 2022).…”
Section: Observable Features Of Gcmsmentioning
confidence: 93%
“…Eclipse mapping is currently the only method by which 2D information can be measured for exoplanets, as outof-eclipse "phase curves" provide low-resolution information as a function of longitude only. 2D spatial information is crucial for understanding atmospheric circulation (Lewis & Hammond 2022), chemical composition (Taylor et al 2020;Yang et al 2023), and cloud structure (Parmentier et al 2016).…”
Section: Introductionmentioning
confidence: 99%